Small-molecule solar cells—status and perspectives - Riede, M; Mueller, T; Tress, W; Schueppel, R; Leo, K (IOP Publishing Ltd, 2008)
In this paper we focus on the current status of organic solar cells based on small molecules. Since their discovery, much progress has been made, and the main steps are highlighted that led to the current state-of-the-art devices. However, organic solar cells still need to be improved further, and the main strategies for improving the power conversion efficiency, namely raising the open circuit voltage Voc and increasing the short circuit current density Jsc, are discussed. In theory, power conversion efficiencies of around 15% should be possible with a single heterojunction; for higher efficiencies, stacked solar cell concepts have to be employed.